Losy Ewangelickiego Zakładu Diakonijnego w Ząbkowicach Śląskich w latach 1945–1946. Przyczynek do dziejów ewangelickiej diakonii żeńskiej na Śląsku - Pawłowski, Kamil (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2019)
The article presents the last years of Evangelical Diaconal Institution in Ząbkowice Śląskie, which was founded in the mid-19th century to care of the sick and children. Chronicles and memoirs stored in the deaconesses archive in Wertheim (Germany) were used as sources
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne